Pacific pioneers : Japanese journeys to America and Hawaii, 1850-80 - Van Sant, John E., 1958- (Asian American experience., 2000)
"Pacific Pioneers profiles the first Japanese who resided in the United States or the Kingdom of Hawaii for a substantial period of time and the Westerners who influenced their experiences." "Pacific Pioneers presents detailed biographical sketches of Japanese such as Joseph Heco, Niijima Jo, and the converts to the Brotherhood of the New Life and introduces the American benefactors, such as William Griffis, David Murray, and Thomas Lake Harris, who built relationships with their foreign visitors. Van Sant also examines the uneasy relations between Japanese laborers and sugar cane plantation magnates in Hawaii during this period and the shortlived Wakamatsu colony of Japanese tea and silk producers in California."--Jacket